The Different Role of Innovation on Indonesian Intra Industry Trade - Alfarisi, Salman; Falianty, Telisa Aulia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to look at the role of differences in innovation between Indonesia and sixty selected partner countries in encouraging bilateral intra-industrial trade (IIT) in the 2009-2017 period with the fixed effect model estimation method (FEM). The innovations in other research generally use RnD spending, number of patents, and other cost-based variables. Whereas in this study using the Global Innovation Index score with the hope of capturing the level of innovation of each country more comprehensively. The results showed that the difference in innovation (DGII) was proven positively and significantly in encouraging IIT Indonesia and partner countries. Control variables, Economic openness (OPEN), GDP average (AGDP), differences in per capita income (DGDPC), and foreign direct investment (FDI) are known to have a positive and significant role in driving IIT. While another control variables, trade cost (TC) have a negative and significant effect in encouraging IIT.Â